PENGARUH ATMOSFER RUANGAN TERHADAP KEPUASAN KONSUMEN DI BALLON D’OR SPORT CAFÉ PADANG PARIAMAN - Yorizal saputra Yorizal Saputra (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
This purpose of research aims to determine the effect Store Atmosphere Against Customer Satisfaction in Ballon D’or Sport Cafe. The type of this research is quantitative descriptive with causal assosiative method which aims to see how big the influence of variable Store Atmosphere (X) on Customer Satisfaction (Y) in Ballon D’or Sport Cafe. The number of samples in this research amounted to 92 people taken using the technique of taking purposive sampling. Data collection technique is done by indirect communication through questionnaire (questionnaire) by using Likert scale that has been tested the validity and reliability. Further data is analyzed through data analysis, simple linear regression analysis through determinant coefficient analysis (R square), using SPSS Computer Program 16.00. The results showed that: (1) Store Atmosphere is in the less good category (59.78%), (2) Customer Satisfaction is in less good category (45,65%), (3) The result of simple linear regression test is obtained with R Square equal to 0,518 with sig level. 0,000 <0.05. This means that the destination image influences the visiting decision significantly by 51.8%, and the remaining 48.2% is influenced by other factors.